Digital Transformations and the Ideological Formation of the Public Sphere: Hegemonic, Populist, or Popular Communication?. (July 2022) - Sevignani, Sebastian
This paper elaborates on a theory of the ideological public sphere in the age of digital media. It describes the public sphere as an initially ascending and then descending communication process that includes both polarising and integrating publics, which are organised by antagonistic media and compromise-building mass media. This framework allows us to distinguish between hegemonic, populist, and popular-oriented flows of communication, as well as register changes in the interplay of different publics driven by digital media platforms. Digital transformations of the public sphere give rise to antagonistic and networked-individualistic flows of populist communication that put public hegemony under constant pressure. The challenge is to find ways to strengthen popular communications that enable democratic learning processes and the flourishing of communicative competences of all citizens.